The Copper Efflux Regulator CueR Is Subject to ATP-Dependent Proteolysis in Escherichia coli - Bittner, Lisa-Marie; Kraus, Alexander; Schäkermann, Sina; Narberhaus, Franz (Frontiers in Molecular Biosciences, 2017)
The trace element copper serves as cofactor for many enzymes but is toxic at elevated concentrations. In bacteria, the intracellular copper level is maintained by copper efflux systems including the Cue system controlled by the transcription factor CueR. CueR, a member of the MerR family, forms homodimers and binds monovalent copper ions with high affinity. It activates transcription of the copper tolerance genes copA and cueO via a conserved DNA-distortion mechanism. The mechanism how CueR-induced transcription is turned off is not fully understood. Here, we report that Escherichia coli CueR is prone to proteolysis by the AAA+ proteases Lon, ClpXP, and ClpAP. Using a set of CueR variants, we show that CueR degradation is not altered by mutations affecting copper binding, dimerization or DNA binding of CueR, but requires an accessible C terminus. Except for a twofold stabilization shortly after a copper pulse, proteolysis of CueR is largely copper-independent. Our results suggest that ATP-dependent proteolysis contributes to copper homeostasis in E. coli by turnover of CueR, probably to allow steady monitoring of changes of the intracellular copper level and shut-off of CueR-dependent transcription.